Kepemimpinan Kepala Sekolah dalam Meningkatkan Efektivitas Pembelajaran Daring pada Masa Pandemi - Apriyani Dwi Pratiwi (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to analyze the principal’s leadership in improving the effectiveness of online learning during the Covid-19 pandemic at SMP Negeri 11 Muaro Jambi. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that the principal’s leadership consists of four main stages: planning, organizing, implementation, and evaluation. The principal adopted a transformational leadership style by providing individualized consideration, motivation, intellectual stimulation, and idealized influence. These strategies were manifested through coordination meetings, teacher training, the use of online learning platforms such as WhatsApp Group, Google Classroom, and Zoom Meeting, as well as regular evaluation of learning activities. Challenges included limited internet access, low digital literacy among some teachers, and fluctuating student motivation. This study emphasizes that the success of online learning during the pandemic is not only determined by the principal’s managerial skills but also by adaptive capacity and transformational leadership.